Organic zinc-rich protective coatings with improved electrochemical properties: The role of nano-powder additions. Issue 1 (1st January 2021) - Jabbar, Murtadha Abbas; Hassan, Azzam D.; Hamza, Zahraa Adnan
Abstract: In this paper, the role of nickel-20 chromium and TiO2 nanoparticles additions for enhancement of corrosion resistance and microhardness of organic zinc-rich coatings were investigated. Three coating samples were prepared by the new additions in different amounts that were experimentally predicted. Particle sizes and coatings micrographs were examined by scanning electron microscope (SEM) and chemical composition was analyzed by energy dispersive spectroscopy (EDS) technique. The corrosion behavior was conducted in 8% concentration HCl by potentiodynamic polarization test and corrosion parameters extracted through Tafel Extrapolation from polarization curves. Microhardness test employed for evaluation the hardness of all obtained coating samples. Results showed that diffusion and dispersion the added nanoparticles through zinc-rich coating (ZRC) improved the hardness of coating significantly. Furthermore, adding nickel-20 chromium nanoparticles to ZRC and incorporation of TiO2 with it, has been shown an enhancement in corrosion resistance by a percentage of 88.7% and 99.8%, respectively.